Predictive modelling of liquid metal divertor: from COMPASS tokamak towards Upgrade. (30th August 2021) - Horacek, J; Cecrdle, J; Tskhakaya, D; Dejarnac, R; Schwartz, J; Komm, M; Cavalier, J; Adamek, J; Lukes, S; Veselovsky, V; Varju, J; Barton, P; et al.
Abstract: Following ELMy H-mode experiments with liquid metal divertor target on the COMPASS tokamak, we predict the behavior of a similar target on COMPASS Upgrade, where it will be exposed to surface heat fluxes even higher than those expected in the future EU DEMO attached divertor. We simulate the heat conduction, sputtering, evaporation, excitation and radiation of lithium and tin in the divertor area. Measured high-resolution data from COMPASS tokamak were rescaled towards the Upgrade based on many established scalings. Our simulation then yields the amount of released metal which ranges from 4 mg s −1 upto 12 g s −1 depending mainly on the geometry and Li/Sn choice, quite independently from active cooling or strike point sweeping.